Diverse Responses of the Bivalve-Killing Dinoflagellate Heterocapsa circularisquama to Infection by a Single-Stranded RNA Virus - Mizumoto, Hiroyuki (American Society for Microbiology (ASM), 2008)
Viruses are believed to be significant pathogens for phytoplankton. Usually, they infect a single algal species, and often their infection is highly strain specific. However, the detailed molecular background of the strain specificity and its ecological significance have not been sufficiently understood. Here, we investigated the temporal changes in viral RNA accumulation and virus-induced cell lysis using a bloom-forming dinoflagellate Heterocapsa circularisquama and its single-stranded RNA virus, HcRNAV. We observed at least three host response patterns to virus inoculation: sensitive, resistant, and delayed lysis. In the sensitive response, the host cell culture was permissive for viral RNA replication and apparent cell lysis was observed; in contrast, resistant cell culture was nonpermissive for viral RNA replication and not lysed. In the delayed-lysis response, although viral RNA replication occurred, virus-induced cell lysis was faint and remarkably delayed. In addition, the number of infectious virus particles released to the culture supernatant at 12 days postinoculation was comparable to that of the sensitive strain. By further analysis, a few strains were characterized as variants of the delayed-lysis strain. These observations indicate that the response of H. circularisquama to HcRNAV infection is highly diverse.